2021
DOI: 10.24926/iip.v12i2.3634
|View full text |Cite
|
Sign up to set email alerts
|

Consumer's Opinion on a Pharmacist's Role in Nutritional Counseling

Abstract: Background: Nutrition has become an increasing health concern. From fad diets to exercise programs, the consumer seems to be consulting multiple resources that all provide a different answer in the process of obtaining optimal health. Easily accessible pharmacists may be the sources to answer crucial nutritional issues facing society today. Methods: Using the results of a previous study about food perceptions among lean and non-lean populations, interview questions were created to determine the populations’ nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Similar findings were found in the United States (US), where only 26% of pharmacists reported offering their patients nutrition-related services such as education and counseling. 22 These contradictory findings show that there may be geographical disparities in pharmacy practices and attitudes toward nutritional therapy. However, the majority of research supports the idea that pharmacists are ready to provide nutritional counseling to patients based on particular observations and prescriptions and are conscious of the importance of incorporating nutritional treatment into patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were found in the United States (US), where only 26% of pharmacists reported offering their patients nutrition-related services such as education and counseling. 22 These contradictory findings show that there may be geographical disparities in pharmacy practices and attitudes toward nutritional therapy. However, the majority of research supports the idea that pharmacists are ready to provide nutritional counseling to patients based on particular observations and prescriptions and are conscious of the importance of incorporating nutritional treatment into patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate exploration of consumers’ opinions about a pharmacist’s role in nutrition counseling, it was identified that consumers do not interact with pharmacists as much as they do with other health professionals on nutrition issues. In part, this was because one-third of the consumers surveyed believed pharmacists lacked proper training to consult on nutrition [ 37 ].…”
Section: Us Policy Developments Advancing Nutrition’s Role In Quality...mentioning
confidence: 99%
“…Pharmacists can guide the public about cost-effective products or alternative therapies to give the best health outcomes for the money spent. 8 The pharmacist can also assist policymakers and decision-makers by providing them with information about cost-effective healthcare treatments, and the effect of diet and nutrition of individuals as well as the public on health-related quality of life. 5 Nutrition-related disorders are on the rise globally and may demand healthcare interventions and hence leading to an increased economic burden on the healthcare system.…”
Section: Providing Cost-effective Nutritionmentioning
confidence: 99%
“…For example, antacid drugs (proton pump inhibitors) increase the risk of malabsorption of zinc, magnesium, iron, and Vitamin B 12 in elderly and malnutrition patients. Meier et al (2021) 8 highlighted that Pharmacology knowledge places a pharmacist in such a special situation to understand drug absorption and food-drug interaction in patients. Such interactions can be critical in the case of the elderly, as well as immune-compromised and critically ill patients.…”
Section: Linkage Of Nutritional Value To Anatomy and Physiologymentioning
confidence: 99%